How to Approach to Torsional Adnexal Mass in a Geriatric Age Woman: A Case Report and Literature Review - ERİN, Recep and TEKİN, Yeşim BAYOĞLU and KOÇAK, Fatma Gülgün (International Journal of Innovative Research in Medical Science, 2019)
We aimed to present how to approach to the postmenopausal torsional adnexal masses, accompanied by a case report and literature review. A 90 year-old geriatric age woman with G5P5 admitted to emergency department with complaints of nausea, vomiting and abdominal pain. We detected a tumoral mass with solid component and irregular surface suspected malignancy in the midline of the pelvis. Laparotomy was performed due to the suspicion of torsion and malignancy. We detected a approximately 25 cm torsional blue-purple colored tumoral mass originating from the right ovary and performed total abdominal hysterectomy and bilateral salpingo-oferectomy. Pathology was reported as a sex cord stromal tumor with torsional. The patient was discharged with complete recovery on the 3rd postoperative day. Adnexal torsion is a gynecologic emergency. It should be considered in postmenopausal women who present with abdominal pain and adnexal mass.